Human rights: The new consensus (London, 1994)
The book deals with five main contents: Review and assess progress made in the field of human rights since the adoptation of the Universal Declarationof Human rights in 1948; Identify obstacles and ways in which they might be overcome; Examine the link between development and enjoyment of economic, social, cultural, civil and political rights; Evaluate the effectiveness of UN methods and mechamisms; Recommend ways to ensure adequate financial and other resources of UN human rights activities
Keywords: human rights